ASSESMENT OF HEAVY METALS IN THE SHOOTS AND ROOTS OF AQUATIC PLANTS AT OWENA RESERVIOR, ONDO STATE - Olawusi-Peters , O. O; Olaniyi, O.A. (Nigerian Journal of Fisheries, 2019)
The balancing and functionality of aquatic ecosystems have shown to depend largely on various aquatic plants. Thus, this study seeks to assess the physico-chemical parameters of water, some heavy metals (Cd, Cu, Fe, Mn, Pb and Zn) in the root and shoot of some aquatic plants in Owena Reservoir so as to provide a baseline information on the pollution status of the aquatic plants in the reservoir. The samples were analyzed using standard methods. The result revealed the physico-chemical properties of water and heavy metals concentration in the aquatic plants to be within the recommended limit. However, there was significant difference (P<0.05) across the period, aquatic plants and parts. The order of bioaccumulation was; Ceratophyllum demersum > Saciolepis africana > Pistia stratiotes. Also, the metal accumulation followed the trend; Cd < Pb < Mn < Cu < Zn < Fe. The result of the study indicate that the study area and species was not polluted and conducive for optimum growth of aquatic organisms. However, proper monitoring of the aquatic environment is hereby recommended so as to avoid potential contamination and destruction of the aquatic flora and fauna.